Intracranial dural arteriovenous fistula presenting like longitudinally extensive transverse myelitis - Widjaya, Ingrid Ayke; Wibawa, Gibran Aditiara; Harlyjoy, Alphadenti; Satyanegara; Yuliatri, Nia (Faculty of Medicine Universitas Indonesia, 2024)
Intracranial dural arteriovenous fistula (DAVF) that drains into spinal perimedullary veins can generate longitudinally extensive transverse myelitis (LETM)-like lesion, which often represents a significant diagnostic and therapeutic challenge. This is a case report of a 50-year-old male referred with all extremity weaknesses. Despite receiving high-dose intravenous steroids for suspected myelitis, no improvement was recorded. Spinal imaging showed abnormal hyperintensity extending from the T6 vertebral level to the medulla, and a flow void lesion from the cervicomedullary junction up to the L3 level. Angiography confirmed a Cognard type V spinal DAVF, which was treated with transarterial embolization of the feeding vessel. Follow-up angiography showed complete occlusion of the fistula without any backflow. Flow voids are no longer visible on MRI conducted 3 weeks post-procedure. Unfamiliarity with these disorders often leads to delays in diagnosis and treatment. Therefore, it is essential to consider intracranial DAVF as a differential diagnosis for LETM-like lesions.